2017
DOI: 10.1080/02642069.2017.1374374
|View full text |Cite
|
Sign up to set email alerts
|

Employee involvement in ideation and healthcare service innovation quality

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…Based on the above finding, we argue that the health service innovation should provide by the local government and the whole staff of the Health Institution in the Sinjai Regency to adapt continuously the innovation health services in the health care system. The results of the results above also supported by some researchers [34], [46], [47], [59], [76]. Others empirically researchers have focused on the health service innovation for examples [34], [40], [41], [65] and they that the innovation in the health service closely indicated to improve the healthcare performance system.…”
Section: Health Service Innovation Effects On Performancesupporting
confidence: 68%
See 2 more Smart Citations
“…Based on the above finding, we argue that the health service innovation should provide by the local government and the whole staff of the Health Institution in the Sinjai Regency to adapt continuously the innovation health services in the health care system. The results of the results above also supported by some researchers [34], [46], [47], [59], [76]. Others empirically researchers have focused on the health service innovation for examples [34], [40], [41], [65] and they that the innovation in the health service closely indicated to improve the healthcare performance system.…”
Section: Health Service Innovation Effects On Performancesupporting
confidence: 68%
“…Beside that, the results also showed that the reliability was also above 0.80 that means all construct have good internal reliability. The hypothesized model of this study has shown in Figure 2 has indicated that the standardized value of the goodness of fit as shown in the Table 4 has been relevance and suitable based on [45], [46] suggestions. The standardized values of the hypothesized measurement and structural model as indicated in the following Figure 3.…”
Section: A Statistical Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Therefore, it is urgent to have an increasingly clear understanding of how digital technologies can act as a promotor of employee creativity in various industries. Specifically, prior studies have demonstrated that ICT can support and trigger employee creativity in a number of industries [10], and specifically in the healthcare sector [13,14]. Beyond ICT-oriented industries, less ICT-oriented organizations and business settings also require employees to perform creatively and can use ICT to trigger this.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Spadotto et al [10] show that new ICT-applications can and should be creatively used in healthcare to enable a further development of the sector. Indeed, a growing body of the new research related to this sector shows that ICT-supported creativity can enable healthcare practices improvement, innovation and operation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%